Loneliness and cardiovascular disease and the role of late‐life depression. (18th April 2017) - Hegeman, Annette; Schutter, Natasja; Comijs, Hannie; Holwerda, Tjalling; Dekker, Jack; Stek, Max; van der Mast, Roos
Abstract : Objective: Loneliness and depression have a strong reciprocal influence, and both predict adverse health outcomes at old age. Therefore, this study examines whether loneliness is associated with the presence of cardiovascular diseases taking into account the role of late‐life depression. Methods: Cross‐sectional data of 477 older adults in the Netherlands Study of Depressed Older Persons were used. Logistic regression analysis was performed to examine the relation between loneliness and cardiovascular disease. Depression was added to the regression model to examine whether depression is an explanatory factor in the association between loneliness and cardiovascular disease. Interaction terms between loneliness and depression and between loneliness and sex were introduced in the regression model to investigate whether depressed and non‐depressed participants, and men and women differed in their association between loneliness and cardiovascular disease. Results: Of the overall group, 61% were lonely, 28% had a history of cardiovascular disease and 74% were depressed. Loneliness and cardiovascular disease were not associated in the overall group after adjustment for confounders (continuous: odds ratio [OR] = 1.04, 95% confidence interval [CI] = 0.98–1.10), p  = 0.25; dichotomous: OR = 1.27, 95% CI = 0.80–2.03, p  = 0.32). For women, there was an association between loneliness and cardiovascular diseases (continuous: OR = 1.13, 95% CI = 1.06–1.21, p  < 0.001; dichotomous: OR = 2.64, 95% CI = 1.50–4.65, p  = 0.001), but this association was not present in men (OR = 0.96, 95% CI = 0.88–1.05, p  = 0.38). This association remained significant after adjustment for confounders, but it lost significance after adding depression to the model. Conclusion: For women only, there was an association between loneliness and cardiovascular disease. However, this association was explained by depression, indicating that loneliness in its own right seems not related with cardiovascular disease. Copyright © 2017 John Wiley & Sons, Ltd.